2022
DOI: 10.1186/s12890-021-01766-2
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating nontuberculous mycobacterium pulmonary disease from pulmonary tuberculosis through the analysis of the cavity features in CT images using radiomics

Abstract: Objective To differentiate nontuberculous mycobacteria (NTM) pulmonary diseases from pulmonary tuberculosis (PTB) by analyzing the CT radiomics features of their cavity. Methods 73 patients of NTM pulmonary diseases and 69 patients of PTB with the cavity in Shandong Province Chest Hospital and Qilu Hospital of Shandong University were retrospectively analyzed. 20 patients of NTM pulmonary diseases and 20 patients of PTB with the cavity in Jinan Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Radiomics may also detect common inflammatory lesions ( 50 , 51 ). Deep learning has been employed ( 25 , 52 , 53 ) to distinguish NTM pulmonary disease and TB, along with use of the cavity characteristics of radiomics to distinguish the two diseases. Consolidation features are common CT features of NTM pulmonary disease and TB.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics may also detect common inflammatory lesions ( 50 , 51 ). Deep learning has been employed ( 25 , 52 , 53 ) to distinguish NTM pulmonary disease and TB, along with use of the cavity characteristics of radiomics to distinguish the two diseases. Consolidation features are common CT features of NTM pulmonary disease and TB.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have built and validated radiomics models based on frequent CT signs such as cavity, TIB, or nodules to differentiate MDR-TB from drug-sensitive TB, and have achieved excellent performance. 10 , 21 Yan et al 22 showed that radiomics features extracted from cavities based on CT images can effectively distinguish nontuberculous Mycobacterium pulmonary disease from pulmonary TB. These studies have effectively demonstrated the association between cavitary radiomic features and the pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, according to the WHO report, it has not improved global case detection rates and shows limited efficacy in extrapulmonary TB (ETB) [ 26 ]. Secondly, The Xpert and PCR laboratory tests are DNA tests of MTBC used to diagnose tuberculosis infection, but they cannot diagnose NTM infection [ 27 ]. Thirdly, the detection limit of Xpert is 131 CFU/ml; any unit lower than this value cannot be detected, resulting in negative results.…”
Section: Discussionmentioning
confidence: 99%